ANALISIS KONSTRUKTIVIS TERHADAP PENGAJUAN PALESTINA SEBAGAI ANGGOTA PENUH PBB TAHUN 2011 - Miranto, Edi (Transformasi, 2012)
Abstract This research was triggered by an act done by Palestine who submission become a full member of the United Nations on September 23, 2011. According to Wendt (1999: 201-202) constructivist approach is the approach based on âideasâ. On the result of this research that the activity of the submission of Palestine as a full member of the United Nations has implications significantly to the identity of Palestine who are struggling became an independent nation and the sovereign. The impacts are, first, successful strategy for internationalization of the Palestinians issue into an international level. Second, increased support of countries on the independence of Palestine. And third, increased support of international public on the independence of Palestine. Keywords: Constructivist Analysis; Palestinian Identity; Full Member Of The United Nations.